Application of Electronic Copyright Management System (ECMS) in Optimizing Digital Copyright Protection on Over-The-Top (OTT) Services in Indonesia - Nadya Simanungkalit; Tasya Safiranita (PALAR | PAKUAN LAW REVIEW, 2026)
Abstract Digital copyright protection in Indonesia still faces major challenges amid the rapid development of increasingly popular Over-The-Top (OTT) services. OTT services facilitate the widespread distribution of creative works, but also increase the potential for digital copyright infringement, such as piracy and unauthorized copying. To overcome this problem, the use of adequate copyright protection technology is needed as an effort to optimize digital copyright protection on OTT services. This study aims to analyze the application of the Electronic Copyright Management System (ECMS) as an effective solution in protecting digital copyright on OTT services in Indonesia. Using normative and comparative legal research methods, this study analyzes the applicable regulations related to digital copyright in Indonesia and compares them with regulations in the United States. The results show that although Indonesia already has regulations on copyright, the existing regulations still do not adequately accommodate the protection of digital copyright and the implementation of security technology. Meanwhile, the United States, through the Digital Millennium Copyright Act (DMCA), has implemented ECMS as a digital copyright security technology. This study proposes the implementation of ECMS in Indonesia to optimize the protection of digital copyright, both preventively and repressively, and provides recommendations for more comprehensive regulatory updates. Keywords: Digital Copyright, Over The Top, ECMS, Copyright Protection, Copyright Infringement